Development of an Antibiotic Guideline for Children With Suspected Ventilator-Associated Infections*. Issue 8 (August 2019) - Shein, Steven L.; Karam, Oliver; Beardsley, Andrew; Karsies, Todd; Prentice, Elizabeth; Tarquinio, Keiko M.; Willson, Douglas F.
Abstract : Objectives: To develop a guideline for the decision to continue or stop antibiotics at 48–72 hours after their initiation in children with suspected ventilator-associated infection. Design: Prospective, multicenter observational data collection and subsequent development of an antibiotic guideline. Setting: Twenty-two PICUs. Patients: Children less than 3 years old receiving mechanical ventilation who underwent clinical testing and initiation of antibiotics for suspected ventilator-associated infection. Interventions: None. Measurements and Main Results: Phase 1 was a prospective data collection in 281 invasively ventilated children with suspected ventilator-associated infection. The median age was 8 months (interquartile range, 4–16 mo) and 75% had at least one comorbidity. Phase 2 was development of the guideline scoring system by an expert panel employing consensus conferences, literature search, discussions with institutional colleagues, and refinement using phase 1 data. Guideline scores were then applied retrospectively to the phase 1 data. Higher scores correlated with duration of antibiotics ( p < 0.001) and higher PEdiatric Logistic Organ Dysfunction 2 scores ( p < 0.001) but not mortality, PICU-free days or ventilator-free days. Considering safety and outcomes based on the phase 1 data and aiming for a 25% reduction in antibiotic use, the panel recommended stopping antibiotics at 48–72 hours for guideline scores less than or equal to 2, continuing antibiotics for scores greater than or equal to 6, and offered no recommendation for scores 3, 4, and 5. The acceptability and effect of these recommendations on antibiotic use and outcomes will be prospectively tested in phase 3 of the study. Conclusions: We developed a scoring system with recommendations to guide the decision to stop or continue antibiotics at 48–72 hours in children with suspected ventilator-associated infection. The safety and efficacy of the recommendations will be prospectively tested in the planned phase 3 of the study. Abstract : Supplemental Digital Content is available in the text.